Integration Of Islamic Values In Indonesian Procedural Text Material Grade VII SMP/MTS - Ramdhaniyah, Istiqomah; Nur, Andini Putri Mochamad; Sabrina, Syafa; Amirullah, Amirullah (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
Indonesian language learning is considered to be lacking or even does not contribute to strengthening the character of students. In fact, Indonesian language learning in junior and senior high schools can be oriented towards strengthening character. This study aims to analyze and integrate Islamic values in Indonesian procedural text lessons for grade VII SMP/MTs. The method used is qualitative with literature study technique with the focus of the study, which is to reveal Islamic values that can be integrated in the text material of Indonesian language procedures of grade VII SMP/MTs as a means of strengthening the character of students. The data sources used were Indonesian procedural texts of grade VII SMP/MTs and literatures related to this topic. This study took 5 examples contained in the structure of the procedure text in the Indonesian language textbook grade VII SMP/MTs. The results of the study found that Islamic values in Indonesian procedural texts of grade VII SMP/MTs include morals or praiseworthy traits, worship, morals, piety to Allah SWT, challenges for the environment, and others and are strengthened through literature sources that take arguments from the Qur'an and hadith. The consequences of the examination can be used as one of the notes to find out the integration of Islamic values in the Indonesian procedural text lessons of grade VII SMP / MTs.   Keywords: Indonesian Language, Integration, Islamic Values, Procedure Text, Character Education